Cluster Analysis of Customer Satisfaction at PT Esta Dana Ventura, Indonesia - ., Syahnaz; Untari, DhianTyas; Nursal, M.Fadhli; Komariah, NengSiti (International Journal of Economics, Business and Management Studies, 2019)
The purpose of this study is to determine the level of customer satisfaction with service attributes at PT. Esta Dana Venture (physical evidence, reliability, responsiveness, assurance, and empathy). This study involved 220 respondents, where research involved PT Esta Dana Ventura consumers in the category of landing credit debtors. Data analysis methods use the Important Performance Analysis (IPA) model. Based on the results of primary data recapitulation, in general, consumers are quite satisfied with the services provided, where the number of the existing performance is greater than the expectation given by consumers. The results of the study show that the variables are the Empathy and Tangible are the first quadrants, which means very good, while the responsiveness and reliability are the second levels which mean they are not too optimal, while the assurance variable as in the third quadrant means that it is still bad. With the results of this study, it is expected that PT Esta Dana Ventura can further optimize its marketing strategy in order to compete with similar companies.